FRI0728 Osteoarthritis and gout: real-world evidence evaluating patient characteristics, treatment patterns, and healthcare utilization. (15th June 2017) - Samuels, S Krasnokutsky; Pillinger, M; Kabadi, S; Taylor, DC; Morlock, R
Abstract : Background: Gout and osteoarthritis (OA) are common in the United States, but little is known about potential associations of OA and hyperuricemia/gout with clinical outcomes. Objectives: This study examined variations in gout severity, management, and healthcare utilization among gout patients with and without OA. Methods: Data were assessed from a survey of US physicians and patient chart audits. Participating physicians managed the care of ≥50 patients with gout annually; chart audits were of their most recent 5 consecutive adult patients with confirmed gout. Gout severity was measured by physician global assessment, flares, organ/joint damage, and tophi. Treatment characteristics, presence of clinician-confirmed OA, and sociodemographic factors were identified. Descriptive and multivariate (stepwise logistic regression) statistics analyzed the differences among gout patients with and without clinician-confirmed comorbid OA, and assessed urate-lowering therapy (ULT) use and gout control. Results: Overall, 1159 charts of gout patients were abstracted (230 w/ OA, 929 w/o; 81% male; 71% white); the proportion of patients aged ≥61 was greater for those with gout and OA than those with gout but without OA (63% vs 32%; P <0.001). Patients with gout and OA had longer mean duration of gout (63 vs 41 months), were more likely to have tophi (44% vs 19%), joint damage (31% vs 11%), and clinician-rated severe gout (31% vs 12%) than those without OA (all P <0.01). Patients with gout and OA were also more likely to receive ULT (89% vs 70%; P <0.01), and among those receiving ULT, OA patients treated with allopurinol received a higher average daily dose (325 mg vs 296 mg; P =0.031). Gout patients with OA were more likely to have additional comorbidities (cardiovascular disease, kidney disease, COPD, depression, diabetes, hyperlipidemia, hypertension, obesity, prostate problems [men]) and have chronic pain than those without OA (all P <0.05). Gout patients with OA reported more office visits (4.0 vs 3.5), were more likely to have an emergency department visit (17% vs 9%), and were more likely to require surgery for gout in the past 12 months (3% vs 0.3%) (all P <0.01). In both groups, ULT use was associated with better gout control, but the specific factors predictive of ULT use and disease control varied between those with and without OA. Conclusions: Gout patients with OA were more likely to have a greater impact on health system spending, with additional comorbidities and more severe gout than those without OA. These data suggest that gout patients with OA constitute a less healthy group in need of more careful monitoring and more aggressive gout management. Acknowledgements: This study was sponsored by AstraZeneca. Disclosure of Interest: S. Krasnokutsky Samuels: None declared, M. Pillinger: None declared, S. Kabadi Employee of: AstraZeneca, D. Taylor Employee of: Ironwood, R. Morlock Consultant for: AstraZeneca, Ironwood, Ardea Biosciences